ANALISIS HUKUM PERTANGGUNGJAWABAN PEMBERIAN GANTI KERUGIAN KONSUMEN AKIBAT PEMBATALAN SEPIHAK FOSFEN MUSIC FESTIVAL 2022 - Fikri Fajar Maulana; Miko Aditiya Suharto (Jurnal Ilmiah Advokasi, 2026)
The increasing number of music festivals in Indonesia presents challenges in consumer protection. This study aims to analyze liability for compensation due to the unilateral cancellation of the Fosfen Music Festival 2022 and to identify obstacles in its implementation. The research employs an empirical juridical method with a qualitative approach through interviews with affected consumers and analysis of legal documents, including the Civil Code and Consumer Protection Law. The findings reveal that the organizer’s breach of contract was caused by poor financial management and lack of transparency, while consumers faced barriers such as low legal awareness, high costs, and small claim values. Moreover, existing legal mechanisms, both litigation and non-litigation, have not been effective in ensuring refund certainty. This study highlights the weak implementation of consumer protection in mass entertainment events and underscores the need for stronger regulation, government oversight, and risk management by event organizers. Keywords: Default, Consumer Protection, Compensation, Music Festival